A randomized controlled trial on the effectiveness of a sexual abuse prevention programme for girls with intellectual disabilities: study protocol. (15th December 2017) - Chodan, Wencke; Häßler, Frank; Reis, Olaf
ABSTRACT: Objective : Sexual abuse is reported to be more prevalent among children with intellectual disabilities (ID), which emphasizes the need for preventive measures to be taken. The few studies on prevention programmes show methodical weaknesses, such as small sample sizes, a lack of a control group, or invalid outcome measures. This study aims to develop and evaluate a sexual abuse prevention programme that is tailored to the needs of girls with ID and that eliminates many of these weaknesses. Method : The study will enrol 120 girls aged 8–12 with mild ID recruited at special schools. After block randomization, the effects of the prevention programme will be examined in a controlled four-time follow-up design. Preventive skills will be assessed in terms of individual changes in measures of knowledge, verbal reports of anticipated behaviour, role plays, and in situ probes. In situ probes will assess participants' behaviour in a realistic setting, with participants being unaware of the evaluation. All assessments will be videotaped and rated by blind raters. Discussion : This study will be the first randomized controlled trial on the effectiveness of a prevention programme for girls with ID using valid outcome measures with a large sample. It will meet the criteria established for evaluation studies of prevention.